Pediatric Palliative Care: Insights into Assessment Tools and Review Instruments - Simonetta Papa; Anna Mercante; Luca Giacomelli; Franca Benini (MDPI AG, 2023)
The proper assessment of needs and outcomes in pediatric palliative care (PPC) is imperative to ensure the best possible service to patients and families. However, given the multidimensional nature of PPC, the low number of patients in this setting, the heterogeneity of diseases, the presence of cognitive impairment in many patients, and the physiological development of children, outcomes can be complex and difficult to measure. Consequently, in this context, the use of standardized and validated tools to assess the needs of children and families, to assess symptom severity, and to estimate the quality of PPC service represent a current need. Even if efforts have been made to standardize approaches and tools for palliative care in adults, to our knowledge, a similar comprehensive assessment of PPC has not yet been conducted to date. This narrative review provides an overview and discusses the evaluation of tools currently applied in PPC, with an educational intent for healthcare providers. We found that several instruments are available to assess different dimensions of PPC. We proposed a classification into eligibility tools, patient and family needs assessment tools, and care assessment tools. At present, two main eligibility tools exist, the PaPaS Scale and the ACCAPED Scale questionnaire. Most of the tools for patient and family needs assessment have not been specifically validated in the PPC setting, and many may be more readily applied in research settings rather than in daily practice. Similar considerations can be made for tools assessing QoL, while tools assessing PPC service quality seem to be easily applied. Efforts to develop new specific tools and validate existing ones are undoubtedly advocated. However, in the patient's best interest, PPC healthcare providers should start using available tools, regardless of their validation status.